Scalable Frequency Selective Surface with Stable Angles of Incidence on a Thin Flexible Substrate - In-Gon Lee; Ic-Pyo Hong (International Journal of Antennas and Propagation)
A band-stop scalable frequency selective surface (FSS) structure that provides stability for an angle of incidence and polarization is designed using the repetitive arrangement of a unit structure miniaturized on a thin dielectric substrate. The designed miniaturized FSS has a hexagonal unit cell of a minimum size of 0.081 λ at 2.5 GHz in which a triangular loop is repeated. In addition to the frequency stability, the proposed structure reduces the design complexity that is the biggest shortcoming of the miniaturization techniques studied previously. A scalable FSS structure possessing stable frequency response characteristics over a wide band ranging from 2 to 8 GHz, which is achieved by the control of a single design variable, can be designed. For verification of the proposed structure, FSS structures that operate in the bands of 2.5 GHz, 5 GHz, and 8.2 GHz have been designed and fabricated on a very thin substrate. It has been confirmed that the results of the measurement and simulation correspond well with each other. The designed structures also demonstrate high stability for both the polarized wave and the incidence angle of the incident wave.